135k views
3 votes
2x − y = 3

4x = 6 + 2y

a. infinitely many solutions

b. x = 2, y = 1

c. y = 2x - 3

d. x = 4, y = 5

User Gletscher
by
5.2k points

1 Answer

0 votes

Answer:

a. Infinitely many solutions

Explanation:

The given equations are 2x - y = 3

4x = 6 + 2y

We can use substitution method to solve these system of equations.

2x - y = 3

y = 2x - 3

Now plug in y = 2x - 3 in the second equation, we get

4x = 6 + 2(2x - 3)

4x = 6 + 4x - 6

4x = 4x

Here we get infinitely many solution.

Both the equations are the same.

Thank you.

User Paul Miller
by
6.1k points